Cyberbullying and adolescent mental health: systematic review - Sara Mota Borges Bottino; Cássio M. C. Bottino; Caroline Gomez Regina; Aline Villa Lobo Correia; Wagner Silva Ribeiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Cyberbullying is a new form of violence that is expressed through electronic media and has given rise to concern for parents, educators and researchers. In this paper, an association between cyberbullying and adolescent mental health will be assessed through a systematic review of two databases: PubMed and Virtual Health Library (BVS). The prevalence of cyberbullying ranged from 6.5% to 35.4%. Previous or current experiences of traditional bullying were associated with victims and perpetrators of cyberbullying. Daily use of three or more hours of Internet, web camera, text messages, posting personal information and harassing others online were associated with cyberbullying. Cybervictims and cyberbullies had more emotional and psychosomatic problems, social difficulties and did not feel safe and cared for in school. Cyberbullying was associated with moderate to severe depressive symptoms, substance use, ideation and suicide attempts. Health professionals should be aware of the violent nature of interactions occurring in the virtual environment and its harm to the mental health of adolescents.